Morphological analysis of second-intention wound healing in rats submitted to 16 J/cm 2 λ 660-nm laser irradiation - Gonzaga Ribeiro Maria; Cavalcanti de Albuquerque Ricardo; Santos Barreto Andre; Moreno de Oliveira Vitor; Santos Thalita; Freitas Dantas Carolina (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives : Low-level laser therapy (LLLT) has been extensively applied to improve wound healing due to some biostimulatory properties presented by laser arrays apparently able to accelerate the cicatricial repair of soft tissue injuries. However, many controversial results have been reported in the literature, probably as a result of the wide sort of different protocols of photobiomodulation employed in those experiments. The goal of this study was to investigate the effect of a low-dose protocol of LLT on the intensity of the inflammatory response and the pattern of collagen fibers′ deposition during second-intention wound healing in rodents. Materials and Methods : Standard-sized wounds were carried out in the back of 24 male rats. Half of them underwent LLLT treatment (16 J/cm 2 ) at 660 nm delivered for 7 days. Eight and 14 days after the wounds were performed, the repairing area was removed and stained in HE and Masson′s trichrome, and the inflammatory response, epithelization, and collagen fiber depositions were evaluated. Results : We found that LLLT was able to slightly reduce the intensity of the inflammatory reaction as well as to enhance substantially the epithelization process at both 8 th and 14 th days. In addition, it also appeared to stimulate the deposition of collagen fibers at the final stages of wound healing. Conclusions : The LLLT protocol tested in this study resulted in some improvements in second-intention wound healing in rodents.